New nursing faculty and incivility: applying mindfulness-based strategies - Green, Cheryl (Holistic Nursing Practice, 2018)
Workplace incivility remains a problem within the nursing profession. As nurse leaders, we must recognize and not ignore the complexity of cultures that have adapted incivility into the work environment. Nursing education is a discipline that requires collaborative team work, independent drive, and commitment. New nursing faculty experiencing incivility can use mindfulness-based meditation approaches to cope with uncivil behaviors experienced within the workplace. Nurse educators applying the concepts of mindfulness can learn how to provide themselves self-care by reducing stress, as enhanced daily awareness of peace and calm are incorporated into their lifestyle. Mindfulness provides a realization that control can only be given to other persons when an individual allows or accepts another's negative behaviors. Awareness of the value and importance of oneself can assist the nurse educator experiencing incivility to maintain his or her emotional, physical, and spiritual health despite the volatility of the work environment.
Keywords: Attitude of Health Personnel; Bullying; Faculty, Nursing; Humans; Incivility; Interprofessional Relations; Mindfulness; Stress, Psychological; Universities; Workplace; academia; adult; awareness; bullying; complication; dept.nur; etiology; female; health personnel attitude; human; human experiment; incivility; leadership; lifestyle; male; meditation; mental stress; mindfulness; nursing education; nursing faculty; occupation; organization and management; peer-reviewed; psychology; public relations; self care; standards; stress; teamwork; trends; university; work environment; workplace

Incivility among nursing professionals in clinical and academic environments: emerging research and opportunities - Green, Cheryl (IGI Global, 2018)
Traditionally, nursing is acknowledged as a caring profession and is associated with advocating for others. However, incivility is increasingly occurring amongst nurses, both in the clinical and academic environments, and is causing affected nurses both psychological and physical harm. Incivility Among Nursing Professionals in Clinical and Academic Environments: Emerging Research and Opportunities provides emerging views and consequences surrounding workplace bullying in the healthcare profession including recognizing the signs and symptoms of incivility in the workplace, identifying ways in which affected nurses can seek help, and examining healthy methods of coping with the incivility. Featuring coverage on a broad range of topics such as human resources, therapy, and clinical nursing, this book is ideally designed for nurses, managers, healthcare workers and consumers, hospital and clinical staff, researchers, students, and policymakers.
Keywords: dept.nur

Using case study methodology to explore the role of discrimination in workplace incivility - Green, Cheryl (Journal of National Black Nurses' Association: JNBNA, 2018)
Exclusionary behaviors can be detrimental to the health and well-being of faculty in the workplace. When colleagues are judged by their peers because of the color of their skin, the language they speak, their gender, or who they choose to love (lesbian, gay, bisexual, transgender, asexual, or questioning), affected faculty are left emotionally and physically vulnerable. Institutions of higher learning must set standards of zero tolerance for faculty-to-faculty incivility. With standards taken from each faculty discipline, codes of conduct can be implemented not only at a departmental level, but also throughout the educational system.
Keywords: Discrimination; Exclusionary; Faculty; Humans; Incivility; Interprofessional Relations; Prejudice; dept.nur; peer-reviewed

Using instrumentation in psychiatric nursing to assess documentation of the nursing process for emergent non-psychiatric patient events. - Green, Cheryl (Archives of Psychiatric Nursing, 2018)
Ongoing education of experienced psychiatric nurses is imperative given the historically complex health presentations of psychiatric patients. Psychiatric patients tend to have medical co-morbidities and often do not have the financial resources for preventative health care. The hospitalization for acute psychiatric stabilization, is an opportunity for psychiatric nurses to teach and advocate for patients' physiological and psychological health. Documentation of patients' changes in condition and overall clinical presentation, is necessary to ensure patients' health care needs are met. Copyright © 2018 Elsevier Inc. All rights reserved.
Keywords: *Documentation/st [Standards]; *Inservice Training/mt [Methods]; *Nursing Process; *Psychiatric Nursing; Documentation; Educational Measurement; Educational Measurement/sn [Statistics & Numerical Data]; Hospitalization; Humans; Inservice Training; Nurses; Nursing Process; Nursing process; Patients; Psychiatric Nursing; Psychiatry; Surveys and Questionnaires; adult; article; comorbidity; dept.nur; documentation; education; health care need; hospitalization; human; in service training; mental patient; nurse; nursing process; peer-reviewed; procedures; psychiatric nursing; psychological well-being; questionnaire; standards; statistics and numerical data

Contemporary issues: The pre-licensure nursing student and medication errors. - Green, Cheryl (Nurse Education Today, 2018)
In Modern health care, the creation of cultures of safety for patients is of the upmost importance. Impacting the institutional stabilization of health care facilities safety initiatives, is the preparation of pre-licensure nursing students to safely administer medications to patients. Therefore, preparation of the pre-licensure nursing student must be evidence-based practice focused and incorporate innovative ways to reduce the potential for medication errors. Copyright © 2018. Published by Elsevier Ltd.
Keywords: *Clinical Competence; *Medication Errors/nu [Nursing]; *Students, Nursing; Clinical Competence; Education, Nursing, Baccalaureate; Humans; Licensure, Nursing; Medication Errors; Medication Errors/pc [Prevention & Control]; Medication errors; Pre-licensure nursing students; Prevention; Students, Nursing; adult; clinical competence; dept.nur; drug safety; editorial; evidence based practice center; health care facility; human; licensing; medication error; nursing; nursing education; nursing student; peer-reviewed; prevention and control

Teaching accelerated nursing students’ self‐care: A pilot project - Green, Cheryl (Nursing Open, 2020)
Aim A benchmark of 4 has been determined for the reduction of self-reported stress by nursing students’ status post 5 weeks of holistic educational activities and interventions provided by a nurse educator. Design Provision 5 in the American Nurses Association Code of Ethics for Nurses with Interpretive Statements emphasizes the duty of the nurse to not only promote the health and safety of others, but to self as well (ANA, 2015, Code of ethics with interpretive statements, Nursebooks.org). A self-care for nurses’ pilot project was trialled with 25 accelerated nursing students over the course of 5 weeks. Holistic education programmes were facilitated by a nurse educator uninvolved in providing clinical or classroom education to the students. Methods The Standards for Quality Improvement Reporting Excellence (SQUIRE) guidelines are used in this pilot project as a framework to explore standardization of education of nursing students about self-care in nursing programmes and to promote positive health behaviours and student nurses’ insight into how nurses’ self-care can have an impact on patient outcomes. The self-care pilot project introduced the importance of self-care for the pre-licensure nursing student by teaching healthy eating, physical exercise, the value of sleep, use of positive affirmations and aromatherapy to a cohort of accelerated nursing students over the course of 5 weeks. The Star Model of Knowledge Transformation was the theoretical framework for the pilot study. Two questionnaires were used by the principal investigator to obtain participant data, the Project Participant Questionnaire and the Final-Year Group Questionnaire. Results On completion of the self-care for nurses’ pilot, the nursing students reported a reduction in stress and an increased ability to cope with stress after exposure to different holistic stress reduction strategies. An average benchmark of 4.36 was achieved indicating that the nursing students’ self-care had improved status post the interactive teaching intervention. Self-care taught to pre-licensure nursing students by nurse educators can enhance their self-awareness of the importance of stress reduction and care of themselves while enduring the academic rigour and simultaneous clinical practicum experiences in nursing programmes. Applying self-care behaviours to reduction of stress for nursing students may be of benefit to of students as they transition from the pre-licensure to graduate nurse roles. Hence, teaching health behaviours that are self-protective and contribute to maintaining safe clinical environments for nurses and the patients in their care.
Keywords: dept.nur; nurse educators; nursing students; peer-reviewed; self-care; stress reduction

Narrative orphaned: When grief overwhelms - Green, Cheryl (Journal of Psychiatric and Mental Health Nursing, 2021)
What is known on the subject?: The loss of a parent for an adult can be devastating and can impact other relationships. The adult, in absence of parental love and support, may question their own identity. What this paper adds to existing knowledge?: A narrative is used to explain the adults’ experience of parental death and their new identity of being orphaned. What are the implications for practice?: Increased awareness for adults grieving the loss of a parent(s), as to the normalcy of feeling orphaned Adults grieving the death of a parent(s) are provided resources and support in addressing their grieving process. Abstract: Introduction When a parent dies during their child's adulthood, the life of the adult is altered as the familiarity of parental love and safety changes. The isolation and loneliness penetrates deeply as the orphaned adult must now navigate their world in absence of the most significant people in their lives, their parents. Aim To assist persons affected by parental death in understanding the normalcy of feeling orphaned while grieving. Method The use of a personal narrative to provide mental health support to others. Results The resumption of a routine that existed before parental death is possible, but takes time. Intermittent periods of grief can occur throughout one's life. Discussion When grief interrupts one's ability to function daily and the affected adult has relationships impacted by their parent's death, it is recommended that the adult seek mental health treatment. Implications for Practice Narratives can be used with persons affected by parental loss, to provide an example of normal versus complicated grieving and identify when mental health treatment is needed. © 2020 John Wiley & Sons Ltd
Keywords: Adaptation; Adult; Child; Emotions; Grief; Humans; Loneliness; Mental Health; Parents; Psychological; adult; child; child parent relation; coping behavior; dept.nur; emotion; grief; human; loneliness; mental health; peer-reviewed

Equity and diversity in nursing education - Green, Cheryl (Teaching and Learning in Nursing, 2020)
Retention and development of ethnically diverse nursing students may be more likely to occur when nursing faculty receive training on factors that can impact academic success. By understanding complex school system dynamics in low-income areas, cultural, linguistic, gender, age, religion, and ethnic differences, students’ strengths can be readily recognized, embraced, and encouraged by nursing faculty. When the necessity of equity and diversity is recognized within nursing education, this may potentially translate to retention and completion of nursing programs by nursing students from diverse backgrounds, thereby increasing diversity within the nursing profession. © 2020 Organization for Associate Degree Nursing
Keywords: Diversity; Equity; Nursing education; Nursing faculty; Nursing students; academic success; article; dept.nur; ethnic difference; female; gender; human; human experiment; lowest income group; male; nursing education; nursing student; occupation; peer-reviewed; religion

Nurses and Patients' Perspectives on Spiritual Health Assessment - Green, Cheryl (Journal of Religion & Health, 2020)
Nurses conduct physical and psychosocial assessments during admissions to healthcare facilities. Patients rely upon nurses to provide support and education during their journey, from periods of health decline to states of optimal wellness. Therefore, nurses are an ideal population to assess spiritual health. The value and necessity of spiritual assessment were explored on an inpatient unit providing medical and palliative care to patients. Two spiritual assessment tools, comprised each of five items, were evaluated by nursing staff and patients. Spiritual Assessment Tool 1 used language that was unaffiliated with religion, nor a belief in God, and Spiritual Assessment Tool 2 used language affiliated with faith and belief in God. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Attitude of Health Personnel; Humans; Nursing Staff; Palliative Care; Patients; Religion; Spirituality; adult; article; dept.nur; health personnel attitude; hospital patient; human; language; nursing staff; palliative therapy; patient; peer-reviewed; religion

The search for support and healing - Green, Cheryl (Research Anthology on Nursing Education and Overcoming Challenges in the Workplace, 2021)
Chapter 6 provides nurses, nurse leaders, and organizations interventions to understand, confront, and eliminate bullying and incivility from the workplace. Emotional intelligence (EI) and cognitive rehearsal are techniques when taught to nurses via in-services provided by organizations, can build awareness of verbal and nonverbal cues used in their communication as well as those of others. By understanding how we communicate and respond to others and vice versa, insight to what are appropriate and inappropriate responses can hold nurses accountable to how they treat one another. The neuroscience of oxytocin release at a biochemical level supports the benefits of organizations investing in the mental and physical health of their employees by empowering them to grow individually and as a collaborative team. © 2021, IGI Global.
Keywords: dept.nur

Examining and Solving Health Disparities in the United States: Emerging Research and Opportunities - Green, Cheryl (Medical Information Science Reference, 2021)
"This book provides awareness and discussion on the topic of inequities in healthcare that impact health disparities"--
Keywords: Health status indicators; United States; Health Status Disparities; Healthcare Disparities; United States; Health services accessibility; dept.nur; economics; Health Services Accessibility; economics; Socioeconomic Factors; Minority Health; United States; faculty_collection

The elderly and the opioid epidemic: A case study - Green, Cheryl A. (Addictive Disorders & Their Treatment, 2017)
Opioid addiction is a problem within the United States that is impacting all age groups. The elderly are a population that is seldom discussed as being affected by opioids. Physiologically, the older adult is more susceptible for complications associated with an alteration in pharmacokinetics and late diagnosis of diseases such as viral hepatitis C. Health promotion for this population is imperative in the prevention and treatment of opioid addiction problems.
Keywords: Article; Hepatitis C virus; United States; aged; boceprevir; buprenorphine plus naloxone; case report; clinical article; creatinine; creatinine blood level; dept.nur; diamorphine; follow up; health care personnel; health promotion; hepatitis C; human; male; medicare; methadone; methadone treatment; older adults; opiate addiction; opioids; oxycodone; priority journal; protein blood level; self report; telaprevir; urea nitrogen blood level; weight reduction

Complimentary Care: When Our Patients Request to Pray. - Green, Cheryl Ann (Journal of Religion and Health, 2018)
Prayer is viewed in modern medicine as a complimentary alternative treatment. However, to many patients, it is a source of hope and comfort. Patients, when facing illness, advanced disease, disability or death, can benefit from prayer. For healthcare providers, comfort with praying with patients can be deemed as unprofessional conduct or blurred therapeutic boundaries, particularly, when prayer is offered to patients' unsolicited by the patient or their family member(s). Therefore, it is imperative that healthcare providers await the request of prayer by the patient before prayer is initiated.
Keywords: *Attitude of Health Personnel; *Delivery of Health Care; *Faith Healing; *Pastoral Care/mt [Methods]; *Religion; *Spirituality; Attitude of Health Personnel; Delivery of Health Care; Faith Healing; Family; Healthcare providers; Humans; Nurse's Role; Nurses; Pastoral Care; Patients; Prayer; Religion; Religion and Medicine; Spirituality; dept.nur; family; health care delivery; health personnel attitude; human; nurse attitude; pastoral care; peer-reviewed; procedures; religion; spiritual healing

Workplace incivility: Nurse leaders as change agents - Green, Cheryl Ann (Nursing Management, 2019)
An abstract is unavailable.
Keywords: Humans; Interprofessional Relations; Leadership; Nursing Staff; Organizational Innovation; Workplace; dept.nur; human; leadership; nursing staff; organization; peer-reviewed; public relations; workplace

Enough Is Enough: Confronting Workplace Bullying and Incivility - Green, Cheryl Ann (Nursing Education Research Conference 2020, 2020)
Keywords: dept.nur; ⛔ No DOI found

Calm in Chaos: Prose on Tensions of Hate and Distrust in Society - Green, Cheryl; Green, Joshua William (Westbow Press, 2019)
Keywords: Hate; Poetry; Poetry; Racism; dept.nur; faculty_collection

Should nursing be considered a STEM profession? - Green, Cheryl; John, Lori (Nursing Forum, 2020)
Background: The National Science and Technology Council developed a 5-year plan in 2013 to ensure that science, technology, engineering, and mathematics (STEM) experienced sustained growth within the United States (US). Nursing is comprised of multiple sciences that include chemistry, physics, biology, microbiology, anatomy and physiology, pharmacology, and the social and behavioral sciences of sociology, developmental lifespan psychology, and psychology. Science, technology, engineering, and math constitute the traditional STEM acronym. Nursing programs graduate nurses with both the rigorous academic coursework and diverse clinical skills necessary to provide patient care. These skills employed by nurses in the clinical setting can serve as the basis for the inclusion of the nursing profession as a STEM-designated profession by the federal government and educational institutions within the US. Problem: Currently, the US government does not acknowledge the profession of nursing as a STEM-designated profession. Acknowledgment of nursing as a STEM profession could potentially make more funding available for nursing education within the US and address nursing shortages both in clinical and academic settings. As well as position professional nurses for careers not only within the health sector but that of business and industry because of nurses’ STEM knowledge. Hence, enhancing the growth of STEM within the US and creating global market economic competitiveness with new innovation development. Approach: In the practice of nursing, nurses apply the sciences, math, and innovative technology in the assessments, diagnoses, and planning of patients’ care. Nurses implement scientifically-based interventions to treat illness and sustain human life and to ultimately evaluate the outcomes of the care provided to patients. Outcomes: Methodologies of evaluation of outcomes of patient care status post nursing interventions (ie, administration of intravenous antibiotics to treat pneumonia) are based upon rationales that have been derived from evidenced-based practice and nursing research; both originating from applied STEM knowledge. Conclusion: The formal designation by the US federal government, for nursing to be recognized as a STEM profession, can increase funding to the nursing profession and enhance the diversity of employment opportunities for nurses in industry and business. Thereby potentially decreasing nursing shortages and bringing national and worldwide recognition to nursing in both academia, industry, business, and clinical settings, as a profession contributing to the science of improvement of the health of all people through STEM knowledge. © 2019 The Authors. Nursing Forum published by Wiley Periodicals, Inc.
Keywords: Humans; Professional Role; STEAM; STEM; Science; classification; dept.nur; education; health care; human; inclusion; innovation; nursing; professional standard; science

Preface - Logan, Isabel; Green, Cheryl (Stabilization Approaches That Empower Clients Through Mental Health Crises, 2023)
Keywords: dept.nur; dept.swk

Stabilization approaches that empower clients through mental health crises - Logan, Isabel; Green, Cheryl A. (IGI Global, 2023)
Mental health practitioners often overlook initial stabilization strategies and interventions when providing evidence-informed approaches in order to get to the so-called “important” or “interesting” part of treatment. For many mental health practitioners, the “important” or “interesting” component...
Keywords: dept.nur; dept.swk

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

Equity, achievement, and thriving in nursing academic progression - Aragon, Sofia; Beauvais, Audrey M.; Friday, Vivienne; Green, Cheryl; Kiger, Anna J.; King, Simmy; Lear, Tina; Mahowald, Jane; McGuill, Gail; Perkins, Danielle; Valdez, Anna Maria; Velasco, Brian; et al. (Teaching and Learning in Nursing, 2020)
Keywords: dept.nur; equity; nursing education; peer-reviewed; progression